(1599) The Economic Reform Policies and their Impacts on The Balance of Payments':Adjustment in Egypt. سياسات الإصلاح الاقتصادي وتأثيراتها على ميزان المدفوعات: التكيف في مصر. - Khalifa, Magdi. (The Institute of National Planning, 2018)
Includes bibliographical references.